A Systematic Review and Meta-analysis of Income Inequality and Crime in Europe: Do Places Matter? - Kim, Bitna (European journal on criminal policy and research, 2022)
While previous synthesis research studies have found income inequality to be the most consistent predictor of crime at the cross-national level, recent comparative research studies in Europe have implied that the magnitudes of income inequality-crime association might be different in cross-national studies depending on sample composition. Employing a systematic review and meta-analysis, this study aimed to systematically estimate the strength and variability of income inequality-crime association in Europe across multiple published articles and to investigate the intervening role of regions in this relationship. Additional analyses were conducted to detect the regional differences within Europe using the official secondary data of 36 European countries. Income inequality in Europe had a small impact on crime (Mr = .171, k = 10), indicating that income inequality accounts for only 3% of the variance in crime outcomes. While the income inequality-crime association was significant in Eastern/Northern Europe, income inequality had little or no effect on crime in Western/Southern Europe. The small association between income inequality and crime in Europe may be due to the well-developed welfare system, which helps to buffer the adverse effects of being poor. This study’s findings highlight the importance of incorporating geographic characteristics into cross-national research using purposive sampling techniques.